2008
DOI: 10.1002/bem.20426
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of seeds to static magnetic field enhances germination and early growth characteristics in chickpea (Cicer arietinum L.)

Abstract: Seeds of chickpea (Cicer arietinum L.) were exposed in batches to static magnetic fields of strength from 0 to 250 mT in steps of 50 mT for 1-4 h in steps of 1 h for all fields. Results showed that magnetic field application enhanced seed performance in terms of laboratory germination, speed of germination, seedling length and seedling dry weight significantly compared to unexposed control. However, the response varied with field strength and duration of exposure without any particular trend. Among the various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 12 publications
5
91
0
3
Order By: Relevance
“…Aladjadjiyan (2010) also ascertained that root and shoot lengths were increased in magnetically treated seeds as compared to untreated seeds. Similarly, Vashisth and Nagarajan (2008) reported that magnetic field application significantly enhanced seed performance in terms of speed of germination, root and shoot length and seedling dry mass compared to unexposed control. Magnetic treatments are assumed to enhance seed vigour by influencing the biochemical processes that involve free radicals, and by stimulating the activity of proteins and enzymes (Kurinobu and Okazaki, 1995).…”
Section: Resultsmentioning
confidence: 90%
“…Aladjadjiyan (2010) also ascertained that root and shoot lengths were increased in magnetically treated seeds as compared to untreated seeds. Similarly, Vashisth and Nagarajan (2008) reported that magnetic field application significantly enhanced seed performance in terms of speed of germination, root and shoot length and seedling dry mass compared to unexposed control. Magnetic treatments are assumed to enhance seed vigour by influencing the biochemical processes that involve free radicals, and by stimulating the activity of proteins and enzymes (Kurinobu and Okazaki, 1995).…”
Section: Resultsmentioning
confidence: 90%
“…Seeds were exposed in batches to static magnetic fields ranging in intervals of 50 mT of from 0 to 250 mT for 1-4 h in steps of 1 hour for all fields. Best results were obtained from exposures of 50 mT for 2 h, 100 mT for 1 h and 150 mT for 2 h (Vashisth et al 2008). Accelerated germination after magnetic stimulation of wheat seeds was observed working with 30, 45 and 60 mT magnetic field strengths (Pietruszewski et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with various researchers, which have been reported for verities of crops. Florez et al (2007), Vashista andNagarajan (2008, 2010) noted a considerable enhancement in germination characteristics such as seedling vigor, shoot and root growth in maize, chickpea and sunflower seeds when treated magnetically. Similarly, Fischer et al (2004) Brought to you by | MIT Libraries Authenticated Download Date | 5/11/18 11:54 AM seed samples.…”
Section: T a B L E 2 Effect Of Different Mf Strengths And Exposure Dmentioning
confidence: 99%